Implikasi Pendidikan Pancasila Terhadap Upaya Pencegahan Kasus Bunuh Diri Remaja - Martini; Marzuki (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The phenomenon of adolescent suicide is a significant and increasing mental health problem in various countries, including Indonesia, influenced by complex social, psychological, and economic pressures. This study aims to analyze the relevance of Pancasila Education in efforts to prevent adolescent suicide cases. The method used is a literature review by analyzing and synthesizing national and international scientific articles published from 2021 to 2025. This study is not yet applied; it only aims to build a theoretical construct regarding the contribution of Pancasila values ​​to adolescent mental health. The results of the study indicate that Pancasila values, namely the values ​​of divinity, humanity, unity, deliberation, and social justice, can build spirituality, empathy, social bonds, communication skills, and a sense of justice in adolescents. The implementation of these values ​​in the character learning process can foster mental resilience, social awareness, and life expectancy, thus Pancasila Education has relevance as a preventive strategy in supporting the prevention of suicide cases in adolescents.